Teachers’ Beliefs, Classroom Practices and Professional Development Towards Socio- scientific Issues - Albe, Virginie (2014)
During the recent past, efforts have been devoted in several countries to introduce socio-scientifi c issues (SSIs) in science curricula in an attempt to democratize science in society and promote scientifi c literacy for all: global climate change and energy systems, genetically modified food, nanotechnologies, gene therapy, pharmaceuticals, etc. Associated with such concerns are debates, for example, about regulation of corporate actions. The educational aim is to prepare students for active participation in society. Empirical research has been performed on pupils’ and students’ reasoning, concept learning, argumentation processes and decision making (for literature review, see Sadler 2004 , 2009 ). The design and analysis of teaching sequences and to a lesser extent the intentions of science teachers for teaching such socio-scientifi c controversies have also been under investigation (Lee et al. 2006 ; Sadler et al. 2006 ). As they have an essential role in supporting the development of young people’s ability to engage with such issues, science teachers’ viewpoints and teaching practices on SSIs also need to be investigated. A key agent of any reform is likely to be the teacher, whose instruction may be infl fenced by her/his general perspectives and awareness of fruitful teaching strategies. Helms ( 1998 ) has noted, for instance, that teachers tend to emphasise teaching and learning of ‘content’ (e.g. laws and theories) because science ‘subject matter’ tends to be highly integrated into their professional identities. Consequently, they may not have strong identities with SSI activities to support citizenship education and research informed activism.